Outcome Mapping FAQs (Outcome Mapping Learning Community)
FAQ resource produced by IDRC's Evaluation Unit, with contributions fr om Kaia Ambrose, Sarah, Earl, Jan Van Ongevalle and Julius Nyangaga. W e've added it here to answer some of your OM related questions.